2018
DOI: 10.3758/s13420-018-0338-x
|View full text |Cite
|
Sign up to set email alerts
|

Inequity aversion in dogs: a review

Abstract: The study of inequity aversion in animals debuted with a report of the behaviour in capuchin monkeys (Cebus apella). This report generated many debates following a number of criticisms. Ultimately, however, the finding stimulated widespread interest, and multiple studies have since attempted to demonstrate inequity aversion in various other non-human animal species, with many positive results in addition to many studies in which no response to inequity was found. Domestic dogs represent an interesting case as,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 170 publications
1
22
1
Order By: Relevance
“…It is, in fact, this whole system that is being conditioned in the classical experiment (Lorenz, quoted in Jenkins et al, 1978; on dogs' exhibition of social behaviours during conditioning experiments, see also Miklósi, 2014, p. 5). Some canine ethologists even suggest that the reward, which plays a key role in conditioning (training), can provoke a form of "aversion for lack of equity" in dogs (McGetrick and Range, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is, in fact, this whole system that is being conditioned in the classical experiment (Lorenz, quoted in Jenkins et al, 1978; on dogs' exhibition of social behaviours during conditioning experiments, see also Miklósi, 2014, p. 5). Some canine ethologists even suggest that the reward, which plays a key role in conditioning (training), can provoke a form of "aversion for lack of equity" in dogs (McGetrick and Range, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the disadvantaged monkey refused to exchange the token, or rejected the cucumber reward entirely, tentatively reminiscent of the behavior of human responders in the impunity game (see below for critical discussion). Since this early study, IA was replicated in capuchin monkeys (van Wolkenten et al, 2007; Fletcher, 2008; Takimoto et al, 2010; Takimoto and Fujita, 2011), and reported in macaques (Massen et al, 2012; Hopper et al, 2013), chimpanzees (Brosnan et al, 2005, 2010), cotton top tamarins (Neiworth et al, 2009), dogs (Range et al, 2009, 2012; Brucks et al, 2016; see McGetrick and Range, 2018 for an overview), wolves (Essler et al, 2017), crows (Wascher and Bugnyar, 2013), rabbits (Heidary et al, 2008) and rats (Oberliessen et al, 2016).…”
Section: Inequity Aversion In Non-human Animalsmentioning
confidence: 98%
“…Many non-human animal species compare payoffs with social partners and display negative responses to inequity (see Brosnan [1], Brosnan and de Waal [2], McGetrick and Range [3], and Oberliessen and Kalenscher [4] for review). Such inequity aversion is thought to counteract exploitation and, consequently, to contribute to the maintenance of cooperation [5][6][7], particularly among non-kin.…”
Section: Introductionmentioning
confidence: 99%
“…Domestic dogs represent a useful model species to further explore the link between inequity aversion and cooperation. Domestic dogs were the first non-primate species found to exhibit inequity aversion and are now one of the best studied species in this field (see McGetrick and Range [3] for review). Range et al [65] reported that when subjects were asked to give their paw in an inequity task (the "paw task"), they stopped complying sooner, and hesitated longer, if their partner received a reward and they themselves did not, compared with the equity condition in which both dogs received an equal reward for the same task.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation